Cellular and molecular immunology - Abbas, Abul K.; Lichtman, Andrew H.; Pillai, Shiv (Elsevier/Saunders, 2015)
Cellular and Molecular Immunology takes a comprehensive yet straightforward approach to the latest developments in this active and fast-changing field. Drs. Abul K. Abbas, Andrew H. Lichtman, and Shiv Pillai present sweeping updates in this new edition to cover antigen receptors and signal transduction in immune cells, mucosal and skin immunity, cytokines, leukocyte-endothelial interaction, and more. In print and online with additional resources, this reference is the up-to-date and readable textbook you need to master the complex subject of immunology. Access the fully searchabl.